Simple Framework for Efficient Development of the Functional Requirement Verification-specific Language - POPIC, S.; TESLIC, N.; BJELICA, M. Z. (Advances in Electrical and Computer Engineering, 2021)
This paper presents the framework for the creation of various domain-specific languages for verification of the functional requirements. When it comes to Requirement Engineering and the process of Validation and Verification of the requirements, there are plenty of tools for modeling, analyzing, and validating the requirements. It comes as a fullblown set of applications for validation of the requirements. But the set of the verification tools is either too complex or usable in a narrow domain. From the customers' point of view, there is a need for another independent requirement verification. This tool enables the creation of the custom verification in a way that allows users (either clients or developers) to verify requirements. It follows the IEEE guides, standards, and best practices to check all aspects of the software requirements that are neither implemented nor checked by the validation process: correctness, completeness, traceability, dependency, importance, and uniqueness. Tool implements design patterns specific to the verification process, thus enabling the faster implementation of the language. The concept can be used for development of the verification-specific language with any type of requirement representation, which will be shown by a few examples. Index Terms--computer languages, formal verification, formal languages, requirement engineering, programming environments.